Pengaruh Profesionalisme, Disiplin Kerja, dan Masa Kerja terhadap Produktifitas Kerja Karyawan di Era New Normal pada PT Trustlog Total Solusindo Surabaya - Rizkiah, Rachmini; Setiadi, Pompong Budi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of professionalism, work discipline, and tenure on employee productivity in a company. This research was conducted on employees at PT Trustlog Total Solusindo, in the city of Surabaya, East Java. The research method used in this research is descriptive by using quantitative methods. This study uses primary data, namely the distribution of questionnaires by taking employee respondents at PT Trustlog Total Solusindo in Surabaya, East Java. This study uses a sample of the total population of the number of employees in the office. The analytical method used is multiple regression analysis which is processed using the SPSS application. The results of this study indicate that the variables of professionalism, work discipline, and tenure have a positive effect on work productivity. And the variables of professionalism, work discipline, and tenure simultaneously affect employee productivity.